HERBICIDAL POTENTIALS OF BOTANICALFOR THE CONTROL OF ALECTRA VOGELII ON GROUNDNUT (Arachis hypogaea L.) VARIETIES IN SUDAN SAVANNA OF NIGERIA - Isah, M.; Ahmad, S. Y.; Shehu, A.; Isah, D. Y.; Balarabe, U. K. (Nigerian Journal of Agriculture and Agricultural Technology, 2026)
A field experiment was carried out during 2018 rainy season at Bayero University Research Farm (11° 57’N, 8°24’E) and Garko, in Garko local government area, Kano State (22°11’N, 68°008’E) to evaluate the effect of groundnut varieties and plant botanicals on the control of Alectra vogelii in the Sudan savanna of Nigeria. The treatments consisted of four (4) groundnut varieties (Kwankwaso, Maibargo, Sabaiya and Samnut-24) and six (6) plant extracts (Azadirachta leaf powder, Tamarind leaf powder, Ficus species leaf powder, Parkia fruit powder, and control). These were factorially combined and laid out in a Randomized Complete Block Design (RCBD) replicated three times. Data were collected on Alectra were number of Alectra infested stands per plot and number of Alectra per stand while on ground nut were pod yield per plant and pod yield per hectare. The results obtained shows that, plant extracts significantly reduced the number of Alectra per stand as compared to control plots while Sabaiya, Maibargo and Samnut-24 have recorded the lowest number of Alectra per stand. Parkia fruit powder and Tamarind leaf powder recorded the highest pod yield, Application of plant extracts significantly reduced the Alectra germination and infestation level. Thus, Tamarind leaf powder along with Sabaiya were found to be effective on Alectra control and produced higher pod yield and can therefore be recommended for Alectra control in the study area.